The development of an early warning system for the Integrated Livestock Production Project (ILP) Tahoua, Niger - Ridder, N.A. de; Bourn, D. (International Livestock Centre for Africa, 1985)
A report of a project study carried in 1985 rainy season (Niger) to collect data for the calibration of satellite imagery at the ground and aerial levels; to make a systematic reconnaissance flight survey to obtain information on livestock population and their distribution after the 1983/84 drought; and to start training of ILP project members on the basic techniques of collection of radioreflectance data.